Menakar Nilai Perusahaan: Uji Kausalitas pada Kepemilikan Institusional dan Kebijakan Hutang - Suwandi, Suwandi; Luju, Elisabet; Melinda, Melinda; Mulyadi, Yose Ega; Akadiati, Victoria Ari Palma; Yulianti, Maria Lusiana; Purwati, Agnes Susana Merry; Abdurohim, Abdurohim (Pusat Riset dan Inovasi Nasional, 2022)
The value of companies in various large companies in Indonesia is still not optimal. This causal study aims to examine the effect of institutional ownership and debt policy on firm value in cosmetics and household sub-sector manufacturing companies on the Indonesia Stock Exchange for the 2015-2021 period. A total of 5 sample companies were identified from a total of 10 companies, so that 35 observational data were collected based on purposive sampling technique. The company's financial statement data is collected through the www.idx.co.id page using documentation techniques. The data that has been collected was analyzed using multiple linear regression. The data was processed using SPSS version 23 program. The results showed that, partially institutional ownership had a negative and significant effect on firm value, while debt policy had a positive and significant effect on firm value. Meanwhile, simultaneously, institutional ownership and debt policy have a significant effect on firm value. Following up on the results of this study, the initial identification of firm value on the Indonesia Stock Exchange should be optimized through the assessment of institutional ownership and debt policy, so as to encourage an increase in firm value.